2003
DOI: 10.1007/s00198-003-1430-3
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and morbidity associated with osteoporosis drug treatment following hip fracture

Abstract: This study examined post-fracture osteoporosis drug treatment in hip fracture patients and the association of treatment with mortality and morbidity. Pre- and post-fracture demographic/health information was collected on a cohort of hip fracture patients aged 65+ years. Post-fracture administrative data on prescription drug use and health care utilization was linked to the cohort data. Five classes of osteoporosis drugs were available during the study period: hormone replacement therapy (HRT), bisphosphonates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
47
2
10

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(64 citation statements)
references
References 14 publications
5
47
2
10
Order By: Relevance
“…Furthermore, although our study examined only the impact of oral bisphosphonates, it confirms and extends the results of the only two non-randomized studies that have tried to examine the relationship between mortality and osteoporosis treatments (that collectively included oral bisphosphonates, estrogen therapy, selective estrogen receptor modifiers, and calcium and Vitamin D supplementation) following hip fracture while overcoming several of their collective limitations [7,9]. The first study by Cree et al examined any post-hip fracture osteoporosis treatment and subsequent mortality in a study of 449 Canadian patients from 1997 to 2001 [7]. In adjusted analyses, any prescribed osteoporosis treatment was associated with reduced mortality over 4 years follow-up (treated patients who died (n=14 [17%]) vs. untreated patients who died (n=158 [44%]); adjusted HR 0.34, 95% CI 0.17, 0.70).…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…Furthermore, although our study examined only the impact of oral bisphosphonates, it confirms and extends the results of the only two non-randomized studies that have tried to examine the relationship between mortality and osteoporosis treatments (that collectively included oral bisphosphonates, estrogen therapy, selective estrogen receptor modifiers, and calcium and Vitamin D supplementation) following hip fracture while overcoming several of their collective limitations [7,9]. The first study by Cree et al examined any post-hip fracture osteoporosis treatment and subsequent mortality in a study of 449 Canadian patients from 1997 to 2001 [7]. In adjusted analyses, any prescribed osteoporosis treatment was associated with reduced mortality over 4 years follow-up (treated patients who died (n=14 [17%]) vs. untreated patients who died (n=158 [44%]); adjusted HR 0.34, 95% CI 0.17, 0.70).…”
Section: Discussionmentioning
confidence: 48%
“…The increased morbidity and mortality extends well beyond the time of convalescence [1][2][3] and includes an increased risk for repeat hip fracture [4,5]. Furthermore, low bone mass is common, though not universal, in hip fracture patients, and osteoporosis is under-diagnosed and undertreated [6][7][8][9]. Treatment with the intravenous bisphosphonate zoledronic acid reduces rates of re-fracture and all-cause mortality in patients with hip fractures [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, current national and international guidelines recommend the use of pharmacological treatments after hip fracture [10,11]. Moreover, the results of several studies showed a decreased mortality rate in patients who were managed with antiosteoporotic drugs as compared with those who were not [12][13][14]. In particular, in the HORIZON study [13] hip fracture patients were randomly assigned to receive annually zoledronic acid either by intravenous infusion or a placebo infusion; both groups received both oral calcium and vitamin D daily.…”
Section: Introductionmentioning
confidence: 99%
“…A Canadian study showed a significant decrease in the mortality of patients treated with antiosteoporotic drugs versus nontreated patients. (5) In a recent international large-scale, randomized, controlled multicenter trial in which hip fracture patients were randomly assigned to receive annual either zoledronic acid by intravenous infusion or a placebo infusion, the secondary endpoint was allcause mortality. (6) Both groups received daily oral calcium and vitamin D. The median follow-up was 1.9 years.…”
Section: Introductionmentioning
confidence: 99%